2015
DOI: 10.1039/c4an02066a
|View full text |Cite
|
Sign up to set email alerts
|

Direct doping analysis of beta-blocker drugs from urinary samples by on-line molecularly imprinted solid-phase extraction coupled to liquid chromatography/mass spectrometry

Abstract: The use of beta-blockers to enhance performance in some sports is forbidden. Based on this regulation, there is a demand for dynamic analytical procedures for analyzing these compounds quickly and without manual sample preparation. Therefore, the use of a molecularly imprinted polymer (MIP) in a multidimensional liquid chromatographic system coupled to a mass spectrometer provides a good alternative for improving the selectivity and practicality of the beta-blocker analyses, as described in this paper. A water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Liquid chromatography/tandem mass spectrometry (LC/MS/MS) is now extensively utilized due to its high selectivity and sensitivity. In addition, many doping analyses are conducted using various extraction methodologies, such as liquid–liquid extraction (LLE), protein precipitation (PP), or solid‐phase extraction (SPE) . SPE presents several advantages over LLE or PP because it includes a relatively simple pre‐treatment procedure and is less dependent on the proficiency of the researcher.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography/tandem mass spectrometry (LC/MS/MS) is now extensively utilized due to its high selectivity and sensitivity. In addition, many doping analyses are conducted using various extraction methodologies, such as liquid–liquid extraction (LLE), protein precipitation (PP), or solid‐phase extraction (SPE) . SPE presents several advantages over LLE or PP because it includes a relatively simple pre‐treatment procedure and is less dependent on the proficiency of the researcher.…”
Section: Introductionmentioning
confidence: 99%
“…Using comprehensive and largely LC‐MS/MS‐based initial testing procedures, the detection of beta‐blockers has not been considered a major issue in sports drug testing lately; nevertheless, a simple on‐line molecular‐imprinted polymer (MIP)‐supported extraction with subsequent LC‐MS/MS analysis was shown to facilitate the detection of a subset of 7 beta‐blockers from human urine. LODs were reported between 1 and 3 ng/mL, representing a competitive approach albeit specifically designed for beta‐blockers only . The in vitro metabolism of a new drug candidate of this class of therapeutics, termed TJ0711, was presented by Hu et al .…”
Section: Beta‐blockersmentioning
confidence: 99%
“…LODs were reported between 1 and 3 ng/mL, representing a competitive approach albeit specifically designed for beta-blockers only. [226] The in vitro metabolism of a new drug candidate of this class of therapeutics, termed TJ0711, was presented by Hu et al A total of 34 metabolic products was observed, some of which might be useful for future in vivo data interpretation and, possibly, doping controls. [227]…”
Section: Beta-blockersmentioning
confidence: 99%
“…Therefore, many antihypertensive drugs were made to manage hypertension and mainly used for managing hypertension and other disorders like heart failure, myocardial infarction, and diabetic nephropathyare angiotensin II receptor [1]. They can be used alone, or together with diuretics, angiotensin-converting enzyme (ACE) inhibitors [2][3][4], beta blockers [5], or calcium channel blockers [6]. It is believed that they are the suitable alternative for the traditional inhibitors of ACE, because of their ability to selectively block the angiotensin 1 receptor in the renin-angiotensin system [7].…”
Section: Introductionmentioning
confidence: 99%